DNN‐based distributed sequential uplink processing in cell‐free massive MIMO based on radio stripes. Issue 3 (10th March 2021) - Mishra, Aman Kumar; Ponnusamy, Vijayakumar
Abstract: Cell‐free massive MIMO (mMIMO) has two distinctive advantages: first is, macrodiversity from large numbers of distributed access points and second, interference cancellation from cellular mMIMO is envisioned to be next‐generation wireless technology for beyond 5G. However, its practical deployment is extremely challenging due to large numbers of long cables (economic perspective) and network synchronisation. Cell‐free mMIMO system based on radio stripe (CFMMRS) network is one such architecture of cell‐free mMIMO suitable for practical deployment. This study proposes DNN‐based distributed sequential uplink processing for detecting symbols in the uplink of CFMMRS network architecture. Simulation results show that the proposed algorithm outperforms the traditional iterative soft interference cancellation‐based detection method.